“Teach Syrians how to live here, to communicate, how to exchange information and knowledge”: Interview with Monis Bukhari, Founder and Director of Syrisches Haus (Global Media Journal - German Edition, 2016)
Refugees do heavily rely on (social) media before and during migration, as the article by Anke Fiedler in this GMJ special issue impressively demonstrates. But what happens after refugees have reached their country of destination? Some become media producers like our interviewee, media and social media activist Monis Bukhari from Syria. He is the founder of Syrisches Haus (Syrian House) in Germany, an information platform from and for fellow Syrians who arrived here as refugees. This Facebook group currently has over 132.000 members – a huge part of the Syrian community in Germany. We asked him about his motivation and the goals of Syrisches Haus.
Keywords: Syrisches Haus; refugees; Syrians in Germany; social media